Constructing a 3D interconnected "trap-zap" β-CDPs/Fe-g-C3N4 catalyst for efficient sulfamethoxazole degradation via peroxymonosulfate activation: Performance, mechanism, intermediates and toxicity. (May 2022) - Peng, Wenxing; Liao, Jianjun; Chen, Liqin; Wu, Xiaochen; Zhang, Xiaodong; Sun, Wei; Ge, Chengjun
Abstract: A novel and high-efficiency catalyst Fe doped g-C3 N4 (Fe-g-C3 N4 ) composited with β-cyclodextrin polymers (β-CDPs) was synthesized for activating peroxymonosulfate (PMS). The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) results showed that the catalyst was 3D interconnected porous structure. The degradation rate constant of sulfamethoxazole (SMX) in β-CDPs/Fe-g-C3 N4 +PMS system was estimated to be 0.132 min −1, which was 14.7 times and 2.2 times that of g-C3 N4 +PMS and Fe-g-C3 N4 +PMS system, respectively. In addition, the β-CDPs/Fe-g-C3 N4 exhibited superior degradation performance in a wide pH range (3.0–9.0) and good selectivity in the presence of other inorganic anions and natural organics. Radical scavenging, electron paramagnetic resonance (EPR) and electrochemical measurements indicated that 1 O2 and Fe(V)O were the main active species for SMX degradation in β-CDPs/Fe-g-C3 N4 +PMS system. Moreover, β-CDPs accelerated electron transfer between catalyst and PMS and promoted the generation of reactive oxygen species (ROS) during PMS activation. The loading of β-CDPs increased the yields of Fe(V)O and 1 O2 in the system and limited the leaching of Fe 3+ . In addition, the possible degradation pathways of SMX were described based on the intermediates detected by liquid chromatography-mass spectrometry (LC-MS), and the toxicity of the intermediates was also evaluated. This work investigate the role of β-CDPs in PMS activation for the first time and develop a promising material with potential for water treatment. Graphical abstract: Image 1 Highlights: β-CDPs/Fe-g-C3 N4 catalysts showed excellent peroxymonosulfate catalytic performance. The role of β-CDPs in β-CDPs/Fe-g-C3 N4 +PMS system was clarified. Efficient SMX removal was achieved in the presence of other water substrates. 1 O2 and Fe(V)O, as the main active species, leaded dual non-radical pathway. The toxicity of SMX degradation intermediates to Chlorella was evaluated.